EVOLUSI STRUKTUR GEOLOGI DAERAH SENTOLO DAN SEKITARNYA, KABUPATEN KULON PROGO, PROPINSI DAERAH ISTIMEWA YOGYAKARTA - , M. MIFTACHURROCHMAN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Sentolo Sub-district, Kulon Progo District is an area with a complicated geology features. Interpretation based on DEM SRTM imagery shows lineaments that can be observed either by manual or digital method. Observation based on lineaments from geological structures and morphological features shows that research area has sustained from several times tectonic phases. Identification of lineaments is used for understanding the direction of tectonic phase as well as the age of the forming force, corresponding with the age of rock units that make up the research area.This research is divided into several steps, consists of DEM imagery processing, field checking, and pre-field and field data analysis and interpretation. Generally from old to young, research area is comprised of Tuffaceous Marl Unit and repetition Layered Limestone that are conformably deposited, and on top of both unconformably deposited is Alluvium Deposit. DEM imagery analysis resulting in that research area lineament patterns are relatively trending N â S, E â W, and NW â SE. Research area sustained from compressional tectonic phase twice, first during Late Pliocene with N â S trend and the second one during Pleistocene with NNW â SSE trend.